Historical Materialism and Social Development: Reconstructing a Marxist Theory in the Age of Contemporary Social Theory - Aung, Ye Si Thu (Indonesian Journal of Advanced Research, 2026)
This paper argues that Karl Marx’s theory of historical materialism remains partially valid and analytically fruitful when reformulated in dialogue with contemporary social theory. After clarifying social development, it reconstructs the core claims of forces and relations of production, class struggle, and modes of production. It examines failed empirical predictions, doubts about socialism or communism, objections to economic reductionism, and concerns about Eurocentrism. By placing historical materialism into conversation with structural functionalism, conflict theory, interpretive approaches, rational-choice and biosocial accounts, it proposes a non-teleological, multi-causal reconstruction retaining its explanatory core for digital capitalism and global inequality.